Calculation Method of Gravity Center and Moment of Radial Gate - LAN Qin; DUAN Dongxu; LIAO Yuhai; CHENG Zhong (Renmin Zhujiang)
The gravity moment of radial gate is an important factor affecting the opening and closing force.In this paper,the analytical formulas of gravity,gravity center and gravity moment of radial gate are derived theoretically,and the influence of two parameters of its gravity center (radius rG and inclination θG) on its opening and closing force are analyzed.On these basis,a simple method for calculating its gravity center is presented.Taking the spillway radial gate and spillway tunnel radial gate of Pankou hydropower station as examples,the rationality and superiority are verified.The results show that compared with the results of empirical formula and 3d model,combination method and rotation method have the advantages of high accuracy and versatility;rotation method is more convenient than the combination method and is an optimal calculation method for gravity center of radial gate.In the two parameters of center of gravity,radius rG has a greater influence on the opening and closing force of radial gate,and inclination θG has a less influence on it.The simple calculation formula is suitable for radial gate without local weighting block,which can overcome the disadvantage of complex calculation of rotation method.In order to achieve high precision and efficiency,the applicability and advantages of empirical formula,rotation method and simple method should be comprehensively utilized in the design.